The Social Intelligence Level of School Teachers in East Jerusalem: An Administrative Perspective from Principals and Vice Principals - Khatib, Rula Nemir Faries Ganem; Awar, Bayan Ali Muhammad (Journal of Educational and Psychological Sciences, 2025)
This study aims to examine and analyze the level of social intelligence among schoolteachers in East Jerusalem from the perspective of principals and their deputies. It also seeks to explore differences in their assessments based on variables such as educational stage, type of school, and years of experience. The study employed a descriptive survey methodology and utilized a questionnaire specifically designed for this purpose, applied to a sample of 24 principals and deputy principals. The results revealed that the overall level of social intelligence among teachers was high (mean = 4.32). The domain of relationship management ranked first (4.32), followed by emotional responsiveness (4.29) and social awareness (4.21), all of which were rated as "very high". The findings also revealed statistically significant differences in the domains of relationship management and emotional responsiveness based on gender, in favor of female participants. In contrast, no statistically significant differences were found based on job title or academic qualification. The study concluded with several key recommendations, including: 1. Designing professional training programs for teachers aimed at developing social intelligence skills, particularly in classroom relationship management.2. Empowering school principals to support teachers by fostering a school culture based on positive communication and active participation.3. Integrating components of social intelligence into the performance evaluation criteria of teachers in East Jerusalem schools, thereby enhancing the quality of the educational process.
Keywords: Social intelligence; educational interaction; teaching competencies; emotional awareness